2017
DOI: 10.1111/jen.12384
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of cold hardy grapes to Drosophila suzukii (Diptera: Drosophilidae)

Abstract: Drosophila suzukii (Diptera: Drosophilidae), known commonly as spotted wing drosophila, is a vinegar fly originating from South‐East Asia and a major pest to many soft‐skinned fruits. Due to the species recent arrival in North America in 2008, many fruit varieties are yet untested for susceptibility to infestation. While previous work has focused on Vitis vinifera, this study aimed to determine grape susceptibility of cold hardy varieties based on hybrids of V. labrusca, V. riparia and V. vinifera. Field sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 30 publications
8
37
0
Order By: Relevance
“…Moreover, damage of berries from little accepted varieties turned these more susceptible. Importantly, we show that the pure presence of D. suzukii does not necessarily result in oviposition or successful offspring performance, which is in line with previous research on grapes [3,42] and in another fruit [12].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, damage of berries from little accepted varieties turned these more susceptible. Importantly, we show that the pure presence of D. suzukii does not necessarily result in oviposition or successful offspring performance, which is in line with previous research on grapes [3,42] and in another fruit [12].…”
Section: Discussionsupporting
confidence: 92%
“…For example, sugar content has been previously described to be a relevant parameter for the development of D. suzukii [10]. Previous studies revealed that there is no correlation between oviposition or performance with measured sugar contents ( • Brix) [3,26]. In our study, only ripe berries of tested varieties were used for bioassays.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Susceptibility to infestation is also variety specific and depends mainly on skin hardness, sugar content and acidity levels . Grapes prone to damage might be more sensitive to D. suzukii than intact grapes, in some cases red grapes are reported to be more attractive than white varieties and the sensitivity of the grapes is higher when fully ripened…”
Section: Background: D Suzukii In Swiss Grape Productionmentioning
confidence: 99%